Artificial Intelligence and Education Business-Model Viability: A Systematic Literature Review - Riza Andriani; Hussein Al Muhtadeebillah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Generative artificial intelligence (AI) is now part of the education process. It can explain material, give practice, and answer questions at almost no cost. This raises a question: can providers survive as businesses? The study asks how AI changes their business models, what it disrupts for learners, and what strategies help them adapt. Using a systematic literature review based on PRISMA 2020, the study searched the Springer Nature Link database with nine keyword sets for 2019 to 2026 and analysed 36 of 1,258 records. The review finds four ways AI changes business models: turning data and content into income-earning assets, automating cost and labour, uneven change across institutions, and new market structures. Disruption is real but only partial. Services that mainly transfer knowledge are hit first, while formal providers face a crisis over the trust placed in their assessment and a loss of control over data and content to technology vendors. Based on the dynamic capabilities view, survival comes from how fast providers sense change, seize new value, and reshape their model, not from owning assets. For managers, the main task is to close the speed gap with vendors and rethink what they offer, instead of leaning on defensive rules. In short, survival depends on how fast a provider can move its value to things AI cannot copy.